2014
DOI: 10.1016/j.bios.2013.11.051
|View full text |Cite
|
Sign up to set email alerts
|

A field effect transistor biosensor with a γ-pyrone derivative engineered lipid-sensing layer for ultrasensitive Fe3+ ion detection with low pH interference

Abstract: Field effect transistors have risen as one of the most promising techniques in the development of biomedical diagnosis and monitoring. In such devices, the sensitivity and specificity of the sensor rely on the properties of the active sensing layer (gate dielectric and probe layer). We propose here a new type of transistor developed for the detection of Fe(3+) ions in which this sensing layer is made of a monolayer of lipids, engineered in such a way that it is not sensitive to pH in the acidic range, therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Nevertheless, prior to its implementation in a real device it is required to graft it efficiently on a suitable surface. In this context, we have recently demonstrated that SLM (Single Lipid Monolayer) [18][19][20][21] can be used as efficient organic dielectrics in Field Effect Transistors devices. Respectively we have implemented a methodology that ensures us to have SLM with unprecedented mechanical and electrical properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, prior to its implementation in a real device it is required to graft it efficiently on a suitable surface. In this context, we have recently demonstrated that SLM (Single Lipid Monolayer) [18][19][20][21] can be used as efficient organic dielectrics in Field Effect Transistors devices. Respectively we have implemented a methodology that ensures us to have SLM with unprecedented mechanical and electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly a sample of a free-OH lipid was assembled on an edge-tailored silicon prism to form a self-assembled monolayer (SAM) and then polymerized within the plane of the monolayer by applying a protocol mastered by our group to form 5. [18][19][20][21] The obtained SLM 5 was successfully characterized in situ; prior to grafting the host compound 4, using a homemade Infrared cell placed in an attenuated total reflectance mode Fourier-transform infrared (ATR-FTIR) spectrophotometer (see SI Figure S12). The initiation and propagation of the polymerization in the outer plane was initiated and ensured by the polycondensation of triethoxysilane group with the ester group on the top of the SLM 5 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…[171] Copyright 2013, ACS Publications. [55] single virus (Influenza A), [48] single proteins (Influenza A Virus Hemagglutinin) [158] Aptamer 10 × 10 −12 m (dopamine), [171] 200 × 10 −12 m (α-thrombin) [37] DNA 1 × 10 −15 m (25-mer DNA), [159] 40 × 10 −12 m (18-mer DNA) [92] PNA 10 × 10 −15 m (31-mer DNA) [44] γ-pyrone 50 × 10 −15 m Fe 3+ [126] Thiamine 40 × 10 −12 m (human prion protein PrP c ) [176] Glycan 50 × 10 −18 m (Influenza A Virus Hemagglutinin) [177] Ni 2+ quelated on AB-NTA Single His-tag F1-ATPase motor protein [156] AB-NTA: Nα,Nα-bis(carboxymethyl)-l-lysine. The increase in the mobility of the receptor due to low density improves the probability of falling inside the Debye limit.…”
Section: Alternative Measurement Modesmentioning
confidence: 99%
“…Interestingly, it was previously shown that the mechanical force required to disrupt a self‐assembled monolayer made from 1,2‐bis‐(10,12‐tricosadiynoyl)‐sn‐glycero‐3‐phosphocholine (DC8, 9 PC, or DC‐PC) (SLM, supported lipid monolayer) can be aptly improved, by a factor of ten, after a radical reticulation within the plane of the monolayer . This property has been successfully exploited in the fabrication of field‐effect transistors sensors based on modified SLMs, as ultrathin gate dielectric layers, directly immobilized at the surface of a H‐terminated silicon‐based channel . Additional experiments performed on SLM's arrays fabricated using harsh lift‐off processes, and used as capacitive sensing platform clearly confirmed these improvements .…”
Section: Introductionmentioning
confidence: 99%